Potential of phosphodiesterase 4B inhibition in the treatment of progressive pulmonary fibrosis - Rebecca Keith; Anoop M. Nambiar (Therapeutic Advances in Respiratory Disease)
Idiopathic pulmonary fibrosis (IPF) is often regarded as the archetypal progressive fibrosing interstitial lung disease (ILD). The term “progressive pulmonary fibrosis” (PPF) generally describes progressive lung fibrosis in an individual with an ILD other than IPF. Both IPF and PPF are associated with loss of lung function, worsening dyspnea and quality of life, and premature death. Current treatments slow the decline in lung function but have side effects that may deter the initiation or continuation of treatment. There remains a high unmet need for additional therapies that can be used alone or in combination with current therapies to preserve lung function in patients with IPF and PPF. Phosphodiesterase-4 (PDE4) is an enzyme involved in the regulation of inflammatory processes. Pre-clinical studies have shown that preferential inhibition of PDE4B has anti-inflammatory and antifibrotic effects and a lower potential for gastrointestinal adverse events than pan-PDE4 inhibition. The preferential PDE4B inhibitor nerandomilast demonstrated efficacy in preserving lung function in a phase II trial in patients with IPF and is under investigation in phase III trials as a treatment for IPF and PPF.